Patients with sporadic and familial amyotrophic lateral sclerosis found value in genetic testing. Issue 2 (20th December 2017) - Wagner, Karin N.; Nagaraja, Haikady N.; Allain, Dawn C.; Quick, Adam; Kolb, Stephen J.; Roggenbuck, Jennifer
Abstract: Background: Amyotrophic lateral sclerosis (ALS) is increasingly recognized as a genetic disease. There is no consensus, however, as to the role of genetic testing in the care of the ALS patient. Methods: We conducted a survey to study patient access, attitudes, and experience with ALS genetic testing among patients enrolled in a US ALS registry. Results: Among 449 survey respondents, 156 (34.7%) were offered testing and 105 of 156 (67.3%) completed testing. The majority of respondents with familial ALS (fALS) (31/45, 68.9%) were offered testing, while a minority of respondents with sporadic ALS (sALS) (111/404, 27.5%) were offered testing ( p = .00001). Comparison of mean test experience scores between groups revealed that respondents with fALS were no more likely to report a favorable experience with genetic testing than those with sALS ( p = .51). Respondents who saw a genetic counselor did not have significantly different test experience scores, compared to those who did not ( p = .14). In addition, no differences in test experience scores were observed between those who received positive or negative genetic test results ( p = .98). Conclusion: These data indicate that patients with ALS found value in clinical genetic testing. Abstract : Patients with ALS have found value in clinical genetic testing.